“Violence”: a key word in the narrative of the recent history of Colombia - NAVIA LÓPEZ, Angela (Utopía y Praxis Latinoamericana, 2024)
The objective of this work is to analyze the use of the concept of violence as a key or explanatory word in the narratives of the recent history of Colombia. For its fulfillment, the notion of keywords by Raymond Williams and the history of concepts by Reinhart Koselleck are used as general references to understand the use of a concept in a certain historical period. From this analytical prism, and using a hermeneutical analysis, we turn to three institutional experiences that have narrated the recent conflict: The Commission of 1958, that of 1987 and the Commission for the Clarification of the Truth of 2022. Each one exposes the general characteristics of the use of the concept of violence. This makes it easier to show how the notion of violence has been a means to understand and explain the history of the country. The corollary analysis allows us to highlight the limitations and challenges of using violence as a keyword, opening debates and possibilities for research and discussions in studies on the subject.